ON THE INFLUENCE OF MHD TURBULENCE ON THE STRUCTURE OF THE RADIOGALAXY LOBES - Tsvyk, N. O. (Одеські астрономічні публікації, 2018)
There is considered the evolution of the shape for the radio galaxy lobes of FRI and FRII types from the point of view on changing the configuration of large-scale structure of magnetic field, and energy transport in the turbulent MHD waves. There have been studied the interaction and transformation of waves in the active regions of the lobes, and so studied the role of MHD waves and vortexes in media-mixing processes and in the amplification of the average magnetic field. The transport of low-energy e-CRs responsible for the radio emission in the MHz band (recorded at the UTR-2 and GURT telescopes) is analyzed for the sources like to the Cygnus A and M87. It is shown that the transport of e-CRs mainly corresponds to the diffusion of CRs on MHD and turbulence scatter, and the entrainment of CRs by quasi-regular post-jet flows inside to the lobe. So, the MHz radio emission that observed emphasizes the peculiarities in the lobe which arising when the magnetic field is in reorganization.